Liberdade de consciência, liberdade de cultos : o papel da lei da separação do estado das igrejas (1911) - Alves, Jorge Fernandes (2013)
The Law of Separation of State and Church, a dictatorial law passed on 20th April 1911 by Afonso Costa, Minister of Justice of the Provisional Government, was intended to introduce a «new regime of cults». However, it proved an ill-fated law, leading to practices which collided with the status detained by the Catholic Church in Portuguese society, to become one of the main targets of both counter-revolutionary forces and conservative republican proposals. This paper aims to analyse the main thematic lines of the Law of Separation, as well as explore enlightening complementary interpretations of its implementation, integrating it in the process of laicisation of State and Nation, now radicalised but which had been initiated with a few laws under the administration of the Marquis of Pombal, and particularly with several measures taken during the constitutional liberalism.